Índice inflamatório da dieta ajustado por energia e dismenorreia em adolescentes de São Luís - MA - ARCOVERDE, Fernanda Vieira Lins (2023)
Objective: To evaluate the association between the energy-adjusted dietary inflammatory index (IIDE) and the presence of dysmenorrhea requiring use of medication in adolescents from São Luís - MA. Methods: This is a cross-sectional study with 1263 female adolescents, aged between 18 and 19 years old. The presence of dysmenorrhea was assessed by report of the use of drugs for analgesia by the participant. Food consumption was assessed using the food frequency questionnaire (FFQ), allowing the calculation of the IIDE. The associations between the prevalence of dysmenorrhea and the IIDE, skin color, socioeconomic level, years of schooling, body fat percentage, number of pregnancies, use of hormonal contraceptives, smoking and physical activity were analyzed using a binary logistic regression model. The hierarchical approach was used to define the variables included in the fitted model. Results: Dysmenorrhea had a prevalence of 10.7% in the studied population. The IIDE ranged from -3.08 to 5.77, with a mean of 1.62 (SD +/-1.52) and first and second tertiles of 0.97 and 2.25, respectively. In the final model, the IIDE did not prove to be a statistically significant predictor for the presence of dysmenorrhea in the studied population (p= 0.849; R2Nagelkerke = 0.036). Two other variables had a statistically significant association with the outcome variable, which were the socioeconomic level (C1, C2 D/E) (OR = 0.655; 95% CI: 0.43 – 0.97) and the number of pregnancies (greater or equal to one) (OR=0.136; 95%CI: 0.01-0.99). Conclusion: Dysmenorrhea had a lower prevalence than that reported in the literature, and there was no association between IIDE and this condition in this population. Considering the weight of this association in nutritional recommendations for adolescents, the present study contributes to this important debate.